Small RNA-modulated anaerobic respiration allows bacteria to survive under antibiotic stress conditions - Kim, Dajeong; Bhat, Abhayprasad; Kim, Seon-Kyu; Lee, Soohyun; Ryu, Choong-Min (Frontiers in Cellular and Infection Microbiology, 2024)
Despite extensive knowledge of antibiotic-targeted bacterial cell death, deeper understanding of antibiotic tolerance mechanisms is necessary to combat multi-drug resistance in the global healthcare settings. Regulatory RNAs in bacteria control important cellular processes such as cell division, cellular respiration, metabolism, and virulence. Here, we investigated how exposing Escherichia coli to the moderately effective first-generation antibiotic cephalothin alters transcriptional and post-transcriptional dynamics. Bacteria switched from active aerobic respiration to anaerobic adaptation via an FnrS and Tp2 small RNA-mediated post-transcriptional regulatory circuit. From the early hours of antibiotic exposure, FnrS was involved in regulating reactive oxygen species levels, and delayed oxygen consumption in bacteria. We demonstrated that bacteria strive to maintain cellular homeostasis via sRNA-mediated sudden respiratory changes upon sublethal antibiotic exposure.